Strengthening digital transformation in adult education organisations - Gródek-Szostak, Zofia; Niemczyk, Agata; Siguencia, Luis Ochoa; Suder, Marcin; Handzel, Jarosław A. (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Social inclusion is an important aspect of any society as it helps to create a sense of belonging and togetherness. It allows individuals to form meaningful relationships with others, while enabling them to make a meaningful contribution to their local communities. Social inclusion has many benefits that can help improve the well-being of both the included and the excluded. One of the benefits of social inclusion is increased access to resources such as education, healthcare, employment opportunities, and other basic needs that may be difficult or impossible for some people to access without community or peer support. By providing these resources through community programmes like mentoring initiatives or job training, individuals are more likely to succeed than if they were left on their own without the help of others. Additionally, this support often leads to improved mental health outcomes due to increased self-esteem. Another benefit associated with social inclusion is the reduction of stigma around certain problems, such as poverty or homelessness, by promoting understanding between different social groups. When members of marginalised groups are able to participate fully in mainstream activities, they feel accepted despite their differences from the majority of society, leading to greater empathy on both sides. This article presents experiences from the project Empower adult educators to support digital social inclusion 2022-1-PL01-KA220-ADU-000088404 [DigIN Project], which aims to improve the capacity of educators and adult education organisations to support them in becoming active users of technology.
Keywords: digital inclusion; digitisation; education; management